Aplicação conjunta de processos para melhoria técnica e ambiental da obtenção de nanoceluloses a partir das fibras de dendê - Souza, Nágila Freitas (2018)
The residues of agroindustry have, over the years, been outstanding as an excellent lignocellulosic source. In this context, the fibers of the palm mesocarp (FPMD) have been studied as a source of cellulose and lignin with promising applications. However, pre-treatments are a critical factor for obtaining these macromolecules. Thus, the present study added the steam explosion process in the natural fibers to promote a better defibrillation of the material and facilitate the decomposition of the biomass in the subsequent organosolv (acetosolv and ethanosolv) pre-treatments. It was also possible to obtain crystalline nanocelluloses by substituting the so expensive dialysis step of water by neutralization with dilute sodium hydroxide. The processes involved in obtaining the nanocelluloses resulting from these pre-treatments were also evaluated for their environmental performance, allowing the technical and environmental performance of the entire nanostructures processing chain to be aggregated. The effects of acetic acid, sodium hydroxide, time (pulping acetosolv and ethanosolv) were evaluated using a central rotational compound design (DCCR). The influence of the vapor blast stage on the fiber defibrillation process was confirmed by the results obtained when the same optimized acetosolv pulping condition was applied to the natural fibers (35 min and acetic acid concentration of 80% (m / m)). After optimization, the acetosolv pulping proved to be more effective than etanosolv (60 min and 4% NaOH concentration) for lignin removal. Thus, the steam explosion process applied on natural palm fiber followed by pre-treatment, acetosolv and bleaching, presented better delignification compared to the pre-treatment of ethanosolv applied on the exploded fibers. This fact was evidenced both in the physical-chemical aspects and in the better environmental performance, discussed through the life cycle assessment (LCA) to obtain crystalline nanocellulose (NCC). It was verified that the replacement of the dialysis stage by NaOH neutralization did not affect the physicochemical parameters of the crystalline nanocelluloses (NCCAOH), which presented good crystallinity (68%), attractive aspect ratio (26), high yield (87%), and better thermal stability against dialyzed NCC. The acetosolv pulping also provided fibrillated nanocellulose (NFC) with excellent brightness, stable surface loads (-26 mV) and good crystallinity index (58%).